2014
DOI: 10.1016/j.otsr.2014.05.020
|View full text |Cite|
|
Sign up to set email alerts
|

The Stoppa approach versus the ilioinguinal approach for anterior acetabular fractures: A case control study assessing blood loss complications and function outcomes

Abstract: Level III retrospective case control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
90
1
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 17 publications
4
90
1
13
Order By: Relevance
“…In a series of 55 cases, Cole and Bolhofner 3 , who first defined the AIP approach, first reported that anatomic vascular blockage related to the technique was anastomosis between the obturator vessels and the inferior epigastric artery and these anastomoses are often to be found but they are sometimes of different dimensions. From clinical studies, Cole and Bolhofner 3 who first described the technique and Elmadağ, Güzel et al 9 determined CMVA in every case at rates similar to those of the current study. There are angiographic studies of corona mortis in literature, but angiographic studies only evaluate arterial anastomoses and do not give information about venous connections 16,24 .…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In a series of 55 cases, Cole and Bolhofner 3 , who first defined the AIP approach, first reported that anatomic vascular blockage related to the technique was anastomosis between the obturator vessels and the inferior epigastric artery and these anastomoses are often to be found but they are sometimes of different dimensions. From clinical studies, Cole and Bolhofner 3 who first described the technique and Elmadağ, Güzel et al 9 determined CMVA in every case at rates similar to those of the current study. There are angiographic studies of corona mortis in literature, but angiographic studies only evaluate arterial anastomoses and do not give information about venous connections 16,24 .…”
Section: Discussionsupporting
confidence: 68%
“…When clinical studies are examined, Elmadağ, Güzel et al 9 determined CMVA in all of 17 acetabular fractures operated on with the AIP approach, 70.6% of which were reported as venous and 29.4% as arterial CMVA. In a series of 55 cases, Cole and Bolhofner 3 , who first defined the AIP approach, first reported that anatomic vascular blockage related to the technique was anastomosis between the obturator vessels and the inferior epigastric artery and these anastomoses are often to be found but they are sometimes of different dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are studies comparing the ilioinguinal approach with the Stoppa approach from functional and radiological points of view. [6][7][8] It was shown that the Stoppa approach facilitates quadrilateral surface reduction and the application of a buttress plate to the pelvic girdle. [6][7][8][9][10] Although the methods showed no difference in functional outcomes, the results have been controversial in terms of the amount of bleeding.…”
mentioning
confidence: 99%